Comparison of Renal Artery, Soft Tissue, and Nerve Damage After Irrigated Versus Nonirrigated Radiofrequency Ablation. (January 2015) - Sakakura, Kenichi; Ladich, Elena; Fuimaono, Kristine; Grunewald, Debby; O'Fallon, Patrick; Spognardi, Anna-Maria; Markham, Peter; Otsuka, Fumiyuki; Yahagi, Kazuyuki; Shen, Kai; Kolodgie, Frank D.; Joner, Michael; et al.
<x xml:space="preserve">Abstract</x> Background— The long-term efficacy of radiofrequency ablation of renal autonomic nerves has been proven in nonrandomized studies. However, long-term safety of the renal artery (RA) is of concern. The aim of our study was to determine if cooling during radiofrequency ablation preserved the RA while allowing equivalent nerve damage. Methods and Results— A total of 9 swine (18 RAs) were included, and allocated to irrigated radiofrequency (n=6 RAs, temperature setting: 50°C), conventional radiofrequency (n=6 RAs, nonirrigated, temperature setting: 65°C), and high-temperature radiofrequency (n=6 RAs, nonirrigated, temperature setting: 90°C) groups. RAs were harvested at 10 days, serially sectioned from proximal to distal including perirenal tissues and examined after paraffin embedding, and staining with hematoxylin-eosin and Movat pentachrome. RAs and periarterial tissue including nerves were semiquantitatively assessed and scored. A total of 660 histological sections from 18 RAs were histologically examined by light microscopy. Arterial medial injury was significantly less in the irrigated radiofrequency group (depth of medial injury, circumferential involvement, and thinning) than that in the conventional radiofrequency group (P<0.001 for circumference; P=0.003 for thinning). Severe collagen damage such as denatured collagen was also significantly less in the irrigated compared with the conventional radiofrequency group (P<0.001). Nerve damage although not statistically different between the irrigated radiofrequency group and conventional radiofrequency group (P=0.36), there was a trend toward less nerve damage in the irrigated compared with conventional. Compared to conventional radiofrequency, circumferential medial damage in highest-temperature nonirrigated radiofrequency group was significantly greater (P<0.001). Conclusions— Saline irrigation significantly reduces arterial and periarterial tissue damage during radiofrequency ablation, and there is a trend toward less nerve damage.